Incidence of iron-deficiency anemia and some associated factors in pregnant women in Rapayan District, Ancash, Peru: May 2010 – March 2011 - Libio (2024)
Objective: To know the incidence of iron-deficiency anemia and its associated factors during pregnancy in Rapayan District, Ancash, Peru. Material and methods: A prospective, analytical and longitudinal study was carried pout in 39 pregnant women in Rapayan District, Huari Province, Ancash Department in Peru, between May 2010 and March 2011. Blood samples were taken from every pregnant woman participating, during the three trimesters of pregnancy, in order to measure hemoglobin values and to assess the shape of red blood cells (RBCs). We also collected additional data, such as age, number pf pregnancies, and weight gain during pregnancy. Results: Of the 39 women studied, 15.3% presented with anemia in the first two trimesters, and 10.2% had anemia during the third trimester. Anemia was classified as mild. Most pregnant women with anemia (83.33%) had normocytic RBCs, and 16.7% had microcytic RBCs. Pregnant women with anemia were between 16 and 42 years old, the number of pregnancies was not relevant, and, when assessing weight gain, it was found that anemia occurred in pregnant women who gained less than 9 Kg during pregnancy. Conclusion: Cultural beliefs in this rural population lead to poor adherence to healthcare measures during pregnancy, particularly with respect to good alimentation practices and the use of iron and folic acid supplements, which are supplied free of charge by the Peruvian Ministry of Health. This leads to the important frequency (15.83%) of pregnant women with iron deficiency anemia in this area.